(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article reveals the essence and the structural elements of the management mechanism of financial security of the bank, in particular: subjects and objects of management, the financial interests, goals and objectives of management, principles and functions of management. In addition, in the research process, we determined that the purpose of management of financial security of the вank is to ensure stable financial standing of the bank and eliminate the possibility of influence of external and internal threats to its security. Investigated that the process of management of financial security includes the following stages: provision of information and analysis, monitoring external and internal environment, prediction and prevention of potential threats and risks, a comprehensive diagnostic of the financial security bank, financial security bank, performance monitoring, report generation and recommendations for improving the effectiveness of financial security of the bank. The result of this article is to develop an effective mechanism of financial security of banking institutions, essential for the functioning of which is the timeliness of identifying and addressing threats to financial security of the bank and parallel the effective interaction of all elements of the given mechanism will allow to increase the efficiency of the planned results of banking activities while ensuring a high level of financial security of banking institutions.